2017
DOI: 10.1177/0310057x1704500613
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine-Associated Hyperthermia: A Retrospective Cohort Study of Intensive Care Unit Admissions between 2009 and 2016

Abstract: Dexmedetomidine-associated hyperthermia has not been previously studied. Analysis is warranted to determine whether this potentially dangerous complication is more prevalent than previously realised. We aimed to examine the association between dexmedetomidine and temperature ≥39.5°C, including patient characteristics, temporality and potential risk factors. We conducted a retrospective cohort study of all intensive care unit (ICU) admissions between 1 July 2009 and 31 May 2016 in a tertiary ICU in Australia. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(50 citation statements)
references
References 48 publications
7
43
0
Order By: Relevance
“…Vital parameters: Comparing normal vital parameters (conscious animal) to parameters under anesthetic effects, significant difference was observed, suggesting bradycardia and respiratory depression: (HR-UAE 68 ± SD = 7.86 to HR-N 80 ± SD 3,81) and (RR-UAE 32 ± SD = 3.78; to RR-N 40 ± SD = 3,01), respectively, which is in agreement with previously reported adverse effects, when using alpha-2 agonists (Arnemo et al, 2005;Granholm et al, 2007;Grayson et al, 2017;Pascoe, 2015).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Vital parameters: Comparing normal vital parameters (conscious animal) to parameters under anesthetic effects, significant difference was observed, suggesting bradycardia and respiratory depression: (HR-UAE 68 ± SD = 7.86 to HR-N 80 ± SD 3,81) and (RR-UAE 32 ± SD = 3.78; to RR-N 40 ± SD = 3,01), respectively, which is in agreement with previously reported adverse effects, when using alpha-2 agonists (Arnemo et al, 2005;Granholm et al, 2007;Grayson et al, 2017;Pascoe, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…Hyperthermia -elevated rectal temperatures under anesthetic effects were recorded (36.0 ± SD = 1.79; range: 33 -38.2 Cº), possibility contributed in part by high tropical ambient temperatures. Nevertheless, the use of an alpha-2 agonist is linked to hyperthermia as a collateral effect, as corroborated in studies on several species, including capybaras (Cruz et al, 1998;Grayson et al, 2017;King et al, 2010). When working with hyperthermia-prone capybaras, it is also recommended to have a couple of buckets with water in reach to help control any potential excessive body temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism is uncertain, doses of greater than 1 µg/kg/hr have been associated with probable ADRs in prior case series ( 13 ). It is postulated that centrally acting alpha-2 agonists such as dexmedetomidine alter the expression of noradrenaline, serotonin, and dopamine, the neurotransmitters that mediate hypothalamic regulation of temperature ( 12 ). In animal studies, alpha-2 agonists block the activation of thermogenic premotor neurons, thereby decreasing body temperature.…”
Section: Discussionmentioning
confidence: 99%
“…In mouse models of alpha-2 receptor knockout, this temperature decrease is not observed; it is therefore possible that polymorphisms in these receptors resulting in decreased receptor activity may predispose patients to hyperthermic reactions ( 27 ). Alternatively, dexmedetomidine may induce hyperthermia through dopaminergic blockade such as that associated with neuroleptic malignant syndrome ( 12 ). Other animal models have demonstrated that under different environmental conditions, alpha agonists result in hyperthermia, suggesting that changes in metabolism of neurotransmitters may also be mediated by other unknown external factors ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies reported that certain patients with DEX used for sedation in the intensive care unit developed high temperatures without clear alternative causes [18,19]. DEX-associated hyperthermia mechanisms are currently unknown.…”
Section: Discussionmentioning
confidence: 99%